Association of serum adiponectin with breast cancer: A meta-analysis of 27 case-control studies. Issue 6 (February 2019) - Yu, Zeping; Tang, Shenli; Ma, Hongbing; Duan, Hong; Zeng, Yong
Abstract: Background: Emerging published studies have indicated that adiponectin is involved in tumorigenesis of breast cancer. However, the results of available studies were inconsistent. The aim of this updated meta-analysis was to assess the association of adiponectin with breast cancer. Materials and methods: PubMed, EMBASE, Wanfang databases, and the China National Knowledge Infrastructure (CNKI) were systematically searched from inception to June 2018. The mean difference (MD) with 95% confidence interval (CI) were estimated and pooled to investigate the effect sizes. Results: Twenty-seven eligible articles that met the study criteria were included in the current meta-analysis. Overall, there was an evident inverse association between serum adiponectin levels and breast cancer (MD = −0.29, 95%CI = (−0.38, −0.21), P  < .001). Asian subgroup showed a significant negative association between serum adiponectin concentrations and breast cancer in subgroup analysis by ethnicity (MD = −2.19, 95%CI = (−3.45, −0.94), P  < .001). However, no statistical significance was found in Caucasian subgroup (MD = −0.65, 95%CI = (−1.47, 0.17), P  = 0.12). Additionally, a further subgroup analysis of Asian stratified by menopausal status showed higher concentrations of adiponectin in healthy control group, whether they were premenopausal (MD = −0.85, 95%CI = (−1.50, −0.19), P  = .01) or postmenopausal (MD = −2.17, 95%CI = (−4.17, −0.18), P  = .03). No significant difference was observed concerning the association between serum adiponectin and breast cancer metastasis (MD = −1.56, 95%CI = (−4.90, 1.78), P  = .36). Conclusion: The current meta-analysis suggests that the serum adiponectin may be inversely associated with breast cancer. Decreased serum adiponectin levels in premenopausal women may also be inversely associated with breast cancer risk other than postmenopausal status. In addition, low serum adiponectin levels in Asian women were more likely to be associated with breast cancer risk than Caucasian women.